Unveiling the role of Ndrg1 gene on the oxidative stress induction behind the anticancer potential of styrylquinazoline derivatives - Katarzyna Malarz; Michał Kuczak; Patryk Rurka; Patrycja Rawicka; Anna Boguszewska-Czubara; Josef Jampilek; Jacek Mularski; Robert Musiol; Anna Mrozek-Wilczkiewicz (Scientific Reports)
Abstract This work presents a multifaceted mechanism of the anticancer action of a 2-styrylquinazoline derivative. Extensive analysis of various aspects related to tyrosine kinase inhibition and effects on cellular targets at both the gene and protein levels revealed the potential of this IS20 compound for future research. This study presents a detailed analysis of the relationship between ABL and SRC kinase affecting the inhibition of the EGFR/mTOR signaling pathway in a non-obvious manner. The study was supported by experiments using various molecular biology techniques to confirm the induction of oxidative stress, inhibition of the cell cycle in the G2/M phase and the triggering of cell death via both the apoptosis and autophagy pathways. The cell models included those with different p53 protein status, which affected the cellular response in the form of altered Ndrg1 expression. Finally, the appropriate physicochemical properties of IS20 for adequate bioavailability and toxicity to the body were observed in an in vivo model.